Resistance genes and extracellular proteins relieve antibiotic stress on the anammox process. (1st September 2021) - Fan, Nian-Si; Fu, Jin-Jin; Huang, Dong-Qi; Ma, Yuan-Long; Lu, Zheng-Yang; Jin, Ren-Cun; Zheng, Ping
Highlights: Microbial and genetic responses of anammox process to ETC and SMZ were different. The combined effects of ETC and SMZ was more significant than that of the single. Increase in ARGs and EPS probably relieved the selection pressures of antibiotics. Proteins in EPS provided binding sites for two antibiotics via hydrogen bonds. Abstract: The anaerobic ammonium oxidation (anammox) process is regarded as a promising approach to treat antibiotic-containing wastewater. Therefore, it is urgent to elucidate the effects of various antibiotics on the anammox process. Moreover, the mechanism of extracellular polymeric substance (EPS) as protective barriers to relieve antibiotic stress remain unclear. Therefore, the single and combined effects of erythromycin (ETC) and sulfamethoxazole (SMZ), and interactions between EPS and antibiotics were investigated in this study. Based on a 228-day continuous flow experiment, high concentrations of ETC and SMZ had significant inhibitory effects on the nitrogen removal performance of the anammox process, with the abundances of corresponding antibiotic resistance genes (ARGs) increasing. In addition, the combined inhibitory effect of the two antibiotics on the anammox process was more significant and longer-lasting than that of the single. However, the anammox process was able to quickly recover from deterioration. The tolerance of anammox granules to the stress of low-concentration antibiotics was probably attributed to the increase in ARGs and secretion of EPS. Molecular docking simulation results showed that proteins in EPS could directly bind with SMZ and ETC at the sites of GLU-307, HYS-191, ASP-318 and THR-32, respectively. These findings improved our understanding of various antibiotic effects on the anammox process and the interaction mechanism between antibiotics and proteins in EPS. Graphical abstracts: Image, graphical abstract